A possible general mechanism of the signal transfer switching on the Α//3-interferons expression. 2. The role of the cAMP in the process of the interferon induction - Karpov, A.V. (Биополимеры и клетка, 1999)
The author carries out an analysis of available data concerning the participation of cyclic adenosine 3',5'-monophosphate (cAMP) in the signal transduction pathway on the α/β-inierferons (IFN) expression during the induction process. The cAMP is known to participate in the activation of protein kinasev during the interferon induction as well as of nuclear factors activating specifically the regulating domains, of IFN genes. The cAMP is thought to be a secondary key messenger mediating the signal, for α/β-lFN induction, the first stage of this induction being the local cell membrane deformation caused by diffirent inducers. Проаналізовано літературні дані стосовно участі циклічного аденозин-3' ,5'-монофосфату (cAMP) при передачі сигналу до експресії α/β-інтерферонів (ІФН) у процесі індукції. Описано участь сАМР в активації протеїнкіназ, які беруть участь в індукції, а також ядерних факторів, що специфічно активують регуляторні домени генів ІФН. Висунуто припущення, що сAMP виступає в ролі ключового вторинного месепджера, який опосередковує сигнал до індукції α/β-ІФН, початковим етапом якого є специфічна деформація клітинної мембрани під дією різних індукторів. Проанализированы литературные данные относительно участия циклического аденозин-3',5-монофосфата (сAMP) при передаче сигнала к экспрессии α/β-интерферонов (ИФН) в процессе индукции. Описано участие сАМР в активации протеинкиназ, участвующих в индукции, а также ядерных факторов, специфически активирующих регуляторные домены генов ИФН. Выдвинуто предположение о том., что с AMP выступает в роли ключевогом вторичного мессенджера, опосредующего сигнал к индукции α/β-ИФН, начальным этапом которого является специфическая деформация клеточной мембраны под воздействием различных индукторов.